Politik Oligarki dan Perampasan Tanah di Indonesia: Kasus Perampasan Tanah di Kabupaten Karawang Tahun 2014 - Ananta, Dicky Dwi (UI Scholars Hub, 2016)
This study discusses the land grabbing practiced by political oligarchy at the local level after the New Order. By using qualitative research methods and case study in Karawang, this study attempts to describe how political oligarchy allows the expropriation of land at the local level. This study finds that networking power of the oligarchy as a common practice in the New Order regime is still continued and practiced by local authority decades after its fall. The study in Karawang reveals the way of the local oligarch forced their desire to accumulate wealth by using predatory ways such as maximising state power for the accumulation of individual wealth, distributing money for political means, and deploying violent non-state organizations. Those are made possible due to the weakness of social forces beyond the networking power of the oligarchy to give unobstracted way to seize material resources. This study concludes that the networking power of the oligarchy is still a dominant social force and becomes one of the patterns of local politics in Indonesia, at least as indicated in the operating form of the oligarch in the case of land grabbing in Karawang.